(untitled) (Nepalese Journal of Hospitality and Tourism Management, 2021)
This paper examined the luxury resort hotel employees’ perspectives on the environmental protection programmes initiated by the hotels in Macau, China. The concern for environmental protection is increasing globally in the hospitality industry, especially for big hotels, as they rank highest among the energy consumers compared to the various sectors of the industry. Macao SAR, whose economy is highly dependent upon casinos that reside within numerous hotels, is being developed as a world tourism and leisure centre. This, in turn, further reinforces the need for the examination of environmental protection programmes. Data for this qualitative study was collected through in-depth semi-structured interviews with fifteen participants which were later analysed using the content analysis method. The result shows that the employees of the luxury resort hotel in Macau perceive variously of the performance of the green practices initiated by the hotel, albeit there was a consensus that additional effort on the part of the hotel was needed to further strengthen environmental protection programmes. The implications of this study and the direction for future research have been explained as well.